Helical inversions and phase separations in binary mixtures of cholesteric liquid crystalline molecules. Issue 1 (2nd January 2019) - Matsuyama, Akihiko; Kan, Tatsuaki
ABSTRACT: A mean field theory is introduced to describe a helical inversion in nematic-cholesteric mixtures and binary cholesteric mixtures. Taking into account a chiral coupling between unlike molecules, the helical pitch is derived as a function of orientational order parameters and concentration. We find the conditions of helical inversions for the mixtures and derive the concentration of the helical inversions, depending on the chiral interaction. The numerical results are in agreement with the experimental results. We also examine phase separations on the temperature-concentration plane, including the helical inversions. A large variety of phase separations, such as the two-phase coexistence between a right-handed rich and a left-handed rich phase, etc., are predicted.